2014
DOI: 10.3389/fpsyg.2014.00107
|View full text |Cite
|
Sign up to set email alerts
|

Gaining control: changing relations between executive control and processing speed and their relevance for mathematics achievement over course of the preschool period

Abstract: Early executive control (EC) predicts a range of academic outcomes and shows particularly strong associations with children's mathematics achievement. Nonetheless, a major challenge for EC research lies in distinguishing EC from related cognitive constructs that also are linked to achievement outcomes. Developmental cascade models suggest that children's information processing speed is a driving mechanism in cognitive development that supports gains in working memory, inhibitory control and associated cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 71 publications
2
46
0
Order By: Relevance
“…Clark et al . () found that 3‐year‐olds’ processing speed predicted their skill at mathematics as 5‐year‐olds (Clark, Nelson, Garza, Sheffield, Wiebe et al ., ); similarly, Rose, Feldman and Jankowski (in press) found that 3‐year‐olds’ processing speed predicted their lexical proficiency as 13‐year‐olds. Finally, Kail () showed that for 8‐ to 13‐year‐olds, more rapid processing speed was associated concurrently with greater WM, which predicted scores on a measure of fluid intelligence administered one year later.…”
Section: Introductionmentioning
confidence: 83%
“…Clark et al . () found that 3‐year‐olds’ processing speed predicted their skill at mathematics as 5‐year‐olds (Clark, Nelson, Garza, Sheffield, Wiebe et al ., ); similarly, Rose, Feldman and Jankowski (in press) found that 3‐year‐olds’ processing speed predicted their lexical proficiency as 13‐year‐olds. Finally, Kail () showed that for 8‐ to 13‐year‐olds, more rapid processing speed was associated concurrently with greater WM, which predicted scores on a measure of fluid intelligence administered one year later.…”
Section: Introductionmentioning
confidence: 83%
“…For example, performance on task-switching paradigms in early childhood correlates with other cognitive control tasks, such as Go/No-Go and working memory span tasks (e.g., Chevalier et al, 2012), and loads onto the same latent factor as other cognitive control tasks (e.g., Clark et al, 2014). These findings make it likely that children in our study who did not show proactive profiles of performance instead relied on reactive control, rather than on non-controlled processes.…”
Section: Discussionmentioning
confidence: 99%
“…Some cognitive tests may have overlapping domains, possibly blurring domain-specific differences in the effects of depressive symptoms. This problem is difficult to avoid (e.g., Clark et al, 2014). It is important to understand more about the EF and SOP domains in the context of depressive symptoms, and to try to disentangle which impairment is most prominent because if the impairment is one of EF, it may influence how well a patient responds to a particular treatment (Alexopoulos et al, 2005).…”
Section: Discussionmentioning
confidence: 99%